PENGEMBANGAN PERANGKAT LUNAK ANALISIS BUTIR SOAL DAN ANGKET - Kusumadani, Annur Indra; Prayitno, Baskoro Adi; Sugiharto, Bowo (Pendidikan Biologi, 2012)
ABSTRACT ? The research is aimed to developing an items test and questionnaire analysis software in order that facilitate students of Biology Education Department, Sebelas Maret University who are conducting research in schools  to analyzing the items test and questionnaire. The software is AN Soft 1.0 that has functions to facilitate the user in analyzing the items test and questionnaire. The software is based on Microsoft Visual Foxpro 9.0 with Microsoft Office 2007 and 2010 as controllers. The research is belonged to Research and Development Method (R & D) (Borg, WR and Gall, MD, 1989) with the following research stages. Research and initial data collection, planning, making the initial product, the initial product  test, the initial product improvements, field test, operational and product improvements. The research involves the following trial subjects. (1) The initial test involving an educational expert, visual communication expert, and information technology expert. (2) The small trial group involves 30 students of Biology Education Department, Sebelas Maret University. (3) The large trial group involves 50 students of Biology Education Department, Sebelas Maret University. The data was analyzed using qualitative descriptive approach that describes and interprets the qualitative data. Before the data was analyzed, carried out the quantification of data from the questionnaires and the assessment form then the data was analyzed qualitatively. The interviews data was analyzed qualitatively. The results of field test 1 and 2 showed that there is an increasing percentage of the total score from all aspects. The results of the questionnaire showed that the rate of interesting on AN Soft 1.0 users increased from 85.33% to 89.8% is classified as very strong, the ease of installing Soft AN 1.0 increased from 84.33% to 94.2% is classified as very strong, The ease of operations AN Soft 1.0 increased from 84% to 93.4% is classified as very strong, and the mastery level of AN Soft 1.0 users increased from 81% to 90.6% which is classified as very strong. Based on the results, it was concluded the developing of items test and questionnaire analysis software product can be facilitating users to analysis items test and questionnaire in accordance with the rules of proper instruments analysis. Keywords: The Items Test and Questionnaire Analysis software, Information and Communication Technology, Instrument Assessment, and Evaluation.